Epidemiology of Cervical Injuries in NCAA Football Players. Issue 12 (15th June 2019) - Chung, Andrew S.; Makovicka, Justin L.; Hassebrock, Jeffrey D.; Patel, Karan A.; Tummala, Sailesh V.; Deckey, David G.; Hydrick, Thomas C.; Rubel, Nicolas C.; Chhabra, Anikar
Abstract : Study Design: Descriptive epidemiology study. Objective: The purpose of this study was to describe the epidemiology of cervical spine injuries in collegiate football players. Summary of Background Data: The incidence and etiology of cervical spine injuries in National Collegiate Athletic Association (NCAA) football players has not been well defined in recent years. Methods: The incidence and characteristics of cervical spine injuries were identified utilizing the NCAA-ISP database. Rates of injury were calculated as the number of injuries divided by the total number of athlete-exposures (AEs). AEs were defined as any student participation in one NCAA-sanctioned practice or competition. Results: An estimated 7496 cervical spine injuries were identified. Of these, 85.6% were categorized as new injuries. These occurred at a rate of 2.91 per 10000 AEs. Stingers were most common (1.87 per 10000 AEs) followed by cervical strains (0.80 per 10000 AEs). Injuries were nine times more likely to occur during competition when compared with practice settings. When compared with the regular season, the relative risks of sustaining a cervical spine injury during the preseason and postseason were 0.69 (95% CI 0.52–0.90) and 0.39 (95% CI 0.16–0.94), respectively. The rate of cervical spine injuries was highest in Division I athletes. Direct contact-related injuries were most common, representing 90.8% of all injuries sustained. Injuries were most common in linebackers (20.3%) followed secondarily by defensive linemen (18.2%). Most players returned to play within 24 hours of the initial injury (64.4%), while only 2.8% remained out of play for > 21 days. Conclusion: Fortunately, the rate of significant and disabling cervical spine injuries appears to be low in the NCAA football athlete. The promotion of safer tackling techniques, appropriate modification of protective gear, and preventive rehabilitation in these aforementioned settings is of continued value. Level of Evidence: 4 Abstract : The incidence and etiology of cervical spine injuries in National Collegiate Athletic Association (NCAA) football players has not been well defined in recent years. The rate of significant and disabling cervical spine injuries appears to be low in the NCAA football athlete.